Air permeability measurements of dwellings and building components in Portugal - Pinto, M. (2011)
Ventilation represents a significant part of heat loss in winter, leading to the need to minimize airflow. However, it is absolutely necessary to ensure indoor air quality and the safety of the users and to control the risk of condensation. Ventilation is responsible on average for 30%e40% of energy consumption in air conditioning in Western European buildings. There is great variability in air change rates (ACH [h 1]) from country to country and the minimum value takes into account comfort, sensory and hygrothermal criteria. In Portugal improvements have been made in the air permeability of window frames, but despite the improvements also made in installing mechanical extraction ventilation devices in kitchens and toilets, these often do not guarantee the minimum number of air change rates required. Air permeability tests were recently carried out in five flats with identical construction characteristics, in the same building, with the aim of characterizing the air permeability of buildings and components, in Portugal. These data are particularly useful for improving the design of building components (e.g., windows and roller shutter boxes) and to perform simulations with reliable data.